Teachers’ Role in Developing Independence of Early Childhood Learners: Peran Guru dalam Mengembangkan Kemandirian Anak Usia Dini - Lastari, Cendya; Wati, Mastika; Kompri, Kompri; Astria, Rani; Maruddani, Raoda Tul Jannah (Indonesian Journal of Education Methods Development, 2023)
General Background: Early childhood education is a critical foundation for character development and readiness for formal schooling. Specific Background: One essential competence to be cultivated is independence, which reflects children’s confidence and responsibility in daily tasks. Knowledge Gap: Although prior studies have examined independence in young learners, limited attention has been given to how teachers systematically foster independence through structured daily practices in specific PAUD institutions. Aim: This study aimed to describe the role of teachers in fostering independence among children aged 5–6 years at PAUD Teratai Putih Muaro Jambi. Results: Findings revealed that 75% of children were able to eat independently, 65% could tidy up toys, and 85% could wear shoes without assistance. Teachers acted as facilitators, motivators, and guides by applying consistent routines, gradual guidance, and positive reinforcement. Novelty: The study highlights how practical strategies in everyday routines can effectively stimulate independence, with contextual insights from a local PAUD setting. Implications: These findings emphasize the importance of teacher creativity and collaboration with parents in developing children’s autonomy, providing a useful reference for early childhood educators and policymakers. Highlights: Teachers foster independence through daily structured routines Parental support and learning environment strengthen outcomes Independence emerges through guided practice and motivation Keywords: Teacher Role, Early Childhood, Independence, Autonomy, PAUD